ANALYZING BRAND EQUITY ON PURCHASE INTENTION THROUGH BRAND PREFERENCE OF SAMSUNG SMARTPHONE USER IN MANADO - Emor, Angelina M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Consumers nowadays tend to value a product from its brand. Strong brand equity brings positive effect to the product. Thus, it is assumed that brand equity affects preference and purchase intention as well. Samsung has become popular in the Smartphone market these years. Currently, Samsung holds the place at the top of Android-based Smartphones globally. This research wants to study about the effect of brand equity on purchase intention through brand preference of Samsung Smartphone users in Manado. The method used is Path analysis. This study collects 200 data sample of population who are users of Samsung Smartphone in Manado. The conclusion of this study is that brand equity has positive significant effect on Brand Preference, Brand Equity has positive significant effect on Purchase Intention, and Brand Preference has positive significant effect on Purchase Intention. This indicates that in order to stay as a leader in the industry, the management must keep on improving their brand equity, be aware of global changes, and create technology that is more sophisticated in order to support the brand. Thus, Samsung will always gain customer preference and intention to purchase. Keywords: brand equity, brand preference, purchase intention